(untitled) (Per Musi, 2021)
Considering the instrumental technique an organism in constant transformation, gradually encompassing extended techniques and converting them into traditional ones, this article investigates repetition by sliding, a resource of the guitar technique in which a right-hand finger attacks a string and in the same movement, subsequently, attacks the adjacent string. The analyses and discussions are based on the few texts that mention the resource and on examples from the didactic and concert guitar repertoire. Four situations are exposed in which repetition by sliding is found in the references: arpeggios of various strings, melodic arpeggios, scales and ornaments; finally, two situations of application of the resource that are absent in the bibliography are presented: contrast between voices and rapid movements on adjacent strings.